Multidisciplinary approach to a diabetes insipidus patient with concomitant conditions: a case report - Rathnasiri, Halamba Osini Senara; Karpovich, Yulia Ivanovna; Bogdanovich, Vladimir (International Journal of Research in Medical Sciences, 2026)
This case report details the clinical presentation, diagnostic journey, and management of a middle-aged female, aged 52, who sought medical attention in February 2025 for excessive thirst, frequent urination with excretion of large volumes of urine, and weakness. Laboratory findings and investigations revealed few underlying pathologies, which were subsequently consulted by multiple specialists, including neurologists, ophthalmologists, and internists. The final diagnosis of complete central diabetes insipidus was attributed to the results from water deprivation tests followed by a desmopressin test. The patient was discharged with favourable results from the treatment plan, with directives to consume fluids only when thirsty, adhere to the treatment plan, and follow up with scheduled consultations and repeat laboratory test results. This case highlights the importance of a multidisciplinary approach to tailored diagnostic methods and the necessity of evaluating differential diagnoses before treatment in the context of a unique condition.